Enhancing postharvest quality of bananas: comparative study on the use ZnO and Ag2O nanoparticles and ZnO/Ag2O composites - Aruwajoye, Noluthando Noxolo; Sanusi, Isaac Adeyemi; Aruwajoye, Gabriel Sanjo; Mditshwa, Asanda; Tesfay, Samson Zeray (Frontiers in Sustainable Food Systems, 2025)
The ‘Cavendish’ banana is cultivated for its flavor and nutritional value, but its climacteric nature leads to rapid ripening and reduced shelf life. Preserving postharvest quality is crucial for minimizing losses and ensuring consumer satisfaction. Nanoparticles such as ZnO and Ag2O have shown promise in extending the shelf life and maintaining the quality of perishable fruits. Therefore, this study aimed to evaluate the efficacy of ZnO- and Ag₂O-enriched edible coatings on the postharvest physicochemical quality of ‘Cavendish’ bananas stored at ambient temperature. Bananas were treated with five different formulations: (1) moringa extract alone (MG), (2) moringa extract combined with carboxymethyl cellulose and glycerol (MG + CMC + GLY), (3) carboxymethyl cellulose and glycerol with Ag2O nanoparticles (Ag2O), (4) carboxymethyl cellulose and glycerol with ZnO nanoparticles (ZnO), and (5) carboxymethyl cellulose and glycerol with a combination of Ag2O and ZnO nanoparticles (Ag2O + ZnO). The effects on key quality parameters, including weight loss, color retention, total soluble solids, total acidity, pH, and peel structure, were assessed. At the end of the storage period, the fruits treated with ZnO + Ag₂O nanoparticles demonstrated a significantly lower decay incidence of 44.44% than the control (100%). Similarly, nanoparticle-enriched treatments maintained higher L* (1.46-fold), b*(1.38-fold), and ho (1.11-fold) values than the control treatment. Remarkably, the Ag2O + ZnO composite formulation showed the most significant positive effects on total acidity, pH, and stomatal cell integrity toward improving banana quality. This study highlights the potential of ZnO/Ag2O composites as effective postharvest treatments to enhance banana quality and extend shelf life, providing a promising approach to reduce postharvest losses and ensure fruit quality during storage and transportation.